Natural phytochemicals that affect autophagy in the treatment of oral diseases and infections: A review - Cheng, Xi; Chen, Qianming; Sun, Ping (Frontiers in Pharmacology, 2022)
Autophagy is a critical factor in eukaryotic evolution. Cells provide nutrition and energy during autophagy by destroying non-essential components, thereby allowing intracellular material conversion and managing temporary survival stress. Autophagy is linked to a variety of oral disorders, including the type and extent of oral malignancies. Furthermore, autophagy is important in lymphocyte formation, innate immunity, and the regulation of acquired immune responses. It is also required for immunological responses in the oral cavity. Knowledge of autophagy has aided in the identification and treatment of common oral disorders, most notably cancers. The involvement of autophagy in the oral immune system may offer a new understanding of the immune mechanism and provide a novel approach to eliminating harmful bacteria in the body. This review focuses on autophagy creation, innate and acquired immunological responses to autophagy, and the status of autophagy in microbial infection research. Recent developments in the regulatory mechanisms of autophagy and therapeutic applications in oral illnesses, particularly oral cancers, are also discussed. Finally, the relationship between various natural substances that may be used as medications and autophagy is investigated.